2023
DOI: 10.3389/fpsyg.2023.1266314
|View full text |Cite
|
Sign up to set email alerts
|

In person versus remote cognitive rehabilitation in patients with subjective cognitive decline or neurocognitive disorders: what factors drive patient’s preference?

Sara Bernini,
Elena Ballante,
Federico Fassio
et al.

Abstract: BackgroundTo date, there is still a lack of consensus for identifying the ideal candidate for cognitive telerehabilitation (TR). The main goal of the present study is to identify the factors associated to the preference for either TR or in-person cognitive training (CT) programs in older adults at risk of dementia or with early cognitive impairment.MethodsA sample of 56 participants with subjective cognitive decline or neurocognitive disorders eligible for CT were enrolled at the Dementia Research Center and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Previous studies revealed the role of demographics, clinical conditions and psychosocial variables in modulating rehabilitation outcomes 1 4 . Besides these factors, the latest evidence supported the role of life-long stimulating activities in influencing patients’ attitudes and responses to non-pharmacological interventions in neurological disorders 4 10 . Especially, patients with higher education, higher cognitive commitment to working activities, and spending more time in stimulating leisure activities may rely on greater cognitive and neural reserve during a rehabilitation program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed the role of demographics, clinical conditions and psychosocial variables in modulating rehabilitation outcomes 1 4 . Besides these factors, the latest evidence supported the role of life-long stimulating activities in influencing patients’ attitudes and responses to non-pharmacological interventions in neurological disorders 4 10 . Especially, patients with higher education, higher cognitive commitment to working activities, and spending more time in stimulating leisure activities may rely on greater cognitive and neural reserve during a rehabilitation program.…”
Section: Introductionmentioning
confidence: 99%
“…Life-long exposure to cognitively stimulating activities seems to have a role in enhancing the treatment beneficial effects on both cognitive and motor functions, probably due to the engagement of multimodal domains (e.g. 5 , 10 ). In particular, cognitively stimulating leisure activities such as social activities (for example, going to museums and traveling), and physical activities (for example, sports and dancing), involve the motor-cognitive functions interplay.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed the role of demographics, clinical conditions and psychosocial variables in modulating rehabilitation outcomes [1][2][3][4] . Besides these factors, latest evidence supported the role of life-long stimulating activities in in uencing patients' attitude and response to nonpharmacological interventions in neurological disorders [4][5][6][7][8][9][10] . Especially, patients with higher education, higher cognitive commitment in working activities and spending more time in stimulating leisure activities may rely on greater cognitive and neural reserve during a rehabilitation program.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, patients with higher education, higher cognitive commitment in working activities and spending more time in stimulating leisure activities may rely on greater cognitive and neural reserve during a rehabilitation program. The life-long exposure to cognitive stimulating activities seems to have a role in enhancing the treatment bene cial effects on both cognitive and motor functions, probably due to the engagement of multimodal domains (e.g., 5,6,10 ). In particular, cognitive stimulating leisure activities such as social activities (for example, going to museums, travelling), and physical activities (for example, sports, dancing), involve the motorcognitive functions interplay.…”
Section: Introductionmentioning
confidence: 99%